Gambaran Pengetahuan Masyarakat Dalam Pencegahan Stunting Dan Penerapan UMKM Digital - Yulia Khairina Asharaa; Ayu Syahvitri; Dina Ika Sintia (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The Real Work Lecture (KKN) which was held in Dusun 7 Sei Cabang Kiri, Desa Kepala Sungai, received a lot of good responses from the community. What we do is interact and cooperate with the community and we also organize Gebyar 1 Muharram (GEMAH). Our goal is to focus on the growth and development of children and small businesses in Kepala Sungai Village, Dusun 7 Sei Branch Kiri. Lack of education. Children exist like adults who are already using cell phones due to the influence of online schools, and they become addicted and less motivated to learn. For UMKM in Dusun 7, they still use word of mouth media so that UMKM have not achieved all sales targets. Not taking enough nutrients according to feed, growth and development. Therefore, we will focus on preventing stunting and implementing an increase in Digital UMKM, emphasizing that children will better understand the importance of education for their growth and development, and parents to pay more attention to children's growth and development through a balanced diet and good nutrition, as well as further improvement of UMKM as a source of income to support life. We want the people of Dusun 7 sei, the left branch of the Sungai Kepala Village, to become a village where generations of children are healthy, have a critical mindset, practice ukhuwah Islamiyah and behave like the morals of the Prophet. We also help the community clean up the village such as mosques, community gardens, roads, etc. Keywords: Real Work Lecture (KKN); Stunting; UMKM Digital